Penerapan Model Pembelajaran Problem Based Learning (PBL) Pada Materi Pluralitas Masyarakat Indonesia Untuk Meningkatkan Hasil Belajar Siswa - Oka Nuzula Saleh (Pendidikan IPS FKIP ULM, 2023)
Learning models have been proven to impact student learning outcomes in specific subjects significantly. One of the effective models that teachers consider is problem-based learning (PBL). This study aims to improve students’ learning outcomes in the Plurality of Indonesian Society subject through the PBL learning model at SMP Negeri 1 Jatisari. The research was conducted in class VIII A of SMP Negeri 1 Jatisari in two cycles with two face-to-face meetings. The data collection techniques involved observation using the following instruments: (1) observation of student activities during the learning process; (2) a questionnaire about students' responses to the application of learning models; and (3) student learning outcomes. The findings of this study show that learning with the PBL learning model can enhance student learning outcomes and their understanding of the subject matter. Based on the students' perceptions, the PBL learning model and student learning outcomes can be summarised as follows: (1) student activity in implementing learning has increased, and the teacher's activity is excellent because they are always actively involved in the learning process; (2) the PBL learning model can improve student learning outcomes; and (3) applying the PBL learning model for two cycles can change the mastery of the subject matter among students individually and classically.Keywords: Learning models, problem-based learning, student learning outcomes.